Flexural tests on externally post-tensioned lightweight concrete beams. (1st June 2018) - Kwon, Seung-Jun; Yang, Keun-Hyeok; Mun, Ju-Hyun
Highlights: This study provided valuable data for externally post-tensioned lightweight concrete beams. This study ascertained the safety of the ACI design procedure for these beam types. We discovered a lower ductility of externally post-tensioned beams. The nonlinear analysis procedure including second-order effect was verified. Abstract: The present study examined the flexural behavior of externally post-tensioned lightweight aggregate concrete (LWAC) beams under symmetrical top one-point, two third-point, and analogous uniform loading systems. With respect to the test parameters, eccentricity of prestressing strands and configuration of deviators for the harped strands varied under different loading conditions. All the test beams had the same geometrical dimension and amount of mild longitudinal bars and prestressing strands. The flexural capacity, stress increase ( Δ f ps ) of the unbonded strands at the ultimate state, and displacement ductility ratio ( μ ) measured in the present beams were compared with those of the internally post-tensioned LWAC one-way members. The comparisons clearly indicated that Δ f ps and μ measured in the externally post-tensioned beams were lower than those of the internally post-tensioned one-way members with the same reinforcing index. This trend was independent of the loading type. Although the design equations for Δ f ps specified in American concrete institute (ACI) provision are conservative in the present beams, the safety level exhibits a significant decrease when compared with the results obtained in the internally post-tensioned LWAC beams. The nonlinear analysis indicates a good agreement for the load–displacement with test results, although a slight overestimation in terms of the flexural strength was observed for beams under an analogous uniform load.